2022
DOI: 10.26650/jot.2022.8.1.1078475
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Job Insecurity, Organizational Commitment and Turnover Intention in the COVID-19 Process

Abstract: With the onset of the COVID-19 pandemic, many sectors have begun to be affected. The tourism sector is one such sector and has been heavily affected by restrictions on international movement of. Affected by this situation, hotels have decided to close their doors or have adopted a limited-service approach. For this reason, tourism employees have become unable to see their way in an uncertain process and have encountered different practices such as hourly paid work, being sent on unpaid leave, and being given a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…Similar results were reported in the high-end hospitality industry during the 2009 COVID-19 pandemic, where employment instability negatively impacted organizational commitment and, in turn, turnover intent [64]. This study demonstrated that in government agencies, insider status somewhat moderated the connection between loyalty to the company and a desire to leave.…”
Section: Relationship Between Oc and Tisupporting
confidence: 81%
See 1 more Smart Citation
“…Similar results were reported in the high-end hospitality industry during the 2009 COVID-19 pandemic, where employment instability negatively impacted organizational commitment and, in turn, turnover intent [64]. This study demonstrated that in government agencies, insider status somewhat moderated the connection between loyalty to the company and a desire to leave.…”
Section: Relationship Between Oc and Tisupporting
confidence: 81%
“…Organizational commitment has also been found to considerably influence performance and moderate the association between total job stress and performance. Previous research has shown that workers' perceptions of their organizations' support are favorably associated with their organizational commitment and adversely related to their desire to leave their current positions and turnover intention [63][64][65]. Thus, H6 explains the observed relationship between OC and TI.…”
Section: Discussionmentioning
confidence: 88%
“…Karatepe et al (2022) found that job insecurity intensified job tension, eroding hotel employees’ trust in the organization and exacerbating their propensity to be late and leave work early. Güzel and Ergen (2022) demonstrated that job insecurity had a significantly negative effect on organizational commitment, and organizational commitment was negatively associated with turnover intention.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 98%
“…Ayrıca bu çalışmaya dahil olan 33 çalışmaya ait ayrıntılı bilgiler Tablo 1'de verilmiştir. Bu 33 çalışmadan 11 tanesi, iş güvencesizliğinin çalışan davranışı ve örgütsel çıktılar üzerindeki direkt etkisini incelemiştir (Akgündüz vd., 2017;Akpulat, 2020;Çalışkan ve Özkoç, 2020;Ceylan Esen, 2018;İşbilir Cebe, 2022;Katlav vd., 2021;Özçelik Bozkurt ve Bayram, 2020;Özçelik Bozkurt ve Sezen Doğancılı, 2021;Özdemir Güzel ve Doğanay Ergen, 2022;Polat, 2019;Tellioğlu, 2021). Bahsi geçen çalışmalardan 13 tanesi, dolaylı veya aracı değişkenleri kapsayan model ile yürütülmüşken (Akgunduz ve Eryilmaz, 2018;Aksoy, 2022;Azaklı, 2011;Bouzari ve Karatepe, 2018, 2017Cizreliogullari vd., 2019aCizreliogullari vd., , 2019bDalgıç, 2020;Etyemez, 2016;Etyemez ve Aslan, 2018;Özkoç, 2017;Safavi ve Bouzari, 2020;Safavi ve Karatepe, 2017), sadece 8 çalışmanın modelinde düzenleyici etkiye yer verilmiştir (Arasli vd., 2019;Çalışkan, 2019;Doğantekin, 2020;Dogantekin vd., 2022;Keriman, 2019;Koca, 2022;Üçler, 2018;Üngüren vd., 2021).…”
Section: Yöntemunclassified